Properties of particleboard from juvenile Acacia mangium at 550 kg/m3 with 8% and 12% resin / Mohd Azli Jaafar - Jaafar, Mohd Azli (2004)
This is a research for producing particleboard from Juvenile Acacia mangium wood dust and combine with UF Resin had been cured by heat and pressure. This testing are determine the suitability the combination of Juvenile Acacia mangium wood dust and UF Resin to produce particleboard. Tests are including bending test, thickness swelling and water absorption. These samples are following 8% and 12% of resin content. The result shows that the percentages of resin used are affecting the properties of board.